Quality of Life Among Clients Under Methadone Maintenance Therapy in Methadone Clinics - Neupane, Shrijana; Acharya, Devaka Kumari (Journal of Nursing Education of Nepal, 2023)
Introduction: Methadone maintenance therapy has impacts on quality of life among opioid use disorder clients. It is a widely accepted treatment for opioid dependent clients. The study aimed to assess the quality of life among clients under methadone maintenance therapy in selected centers of Kathmandu.Methods: A descriptive cross-sectional study was conducted among 162 clients recruited through probability and proportionate sampling technique from two methadone clinics of Kathmandu Metropolitan city. The data was collected from August to September 2022, through face to face interview using WHOQOL-BREF which included 26 items. The data was analyzed by using descriptive statistics to calculate frequency, percentage, mean, median, quartiles, and inferential statistics; Chi-square test and Fisher’s exact test to assess association of quality of life and selected variables.Results: The findings of the study showed that overall score of quality of life was 50. Majority of the respondents (68.5%) had above average quality of life. The highest score was in physical domain (51.61) followed by environment (48.57), social (46.66), and lowest score was in psychological domain (46.15). The study showed a statistically significant association between quality of life and age of opioid use (p=.032).Conclusion: Majority of the clients under methadone maintenance therapy has above average quality of life. Quality of life is comparatively higher in physical domain and lower in psychological domain.DOI: https://doi.org/10.62143/4ffeyx83